High throughput SNP chip as cost effective new monitoring tool for assessing invasion dynamics in the comb jelly Mnemiopsis leidyi - Pujolar, José Martin; Limborg, Morten T.; Ehrlich, Moritz; Jaspers, Cornelia (Frontiers in Marine Science, 2022)
High throughput low-density SNP arrays provide a cost-effective solution for population genetic studies and monitoring of genetic diversity as well as population structure commonly implemented in real time stock assessment of commercially important fish species. However, the application of high throughput SNP arrays for monitoring of invasive species has so far not been implemented. We developed a species-specific SNP array for the invasive comb jelly Mnemiopsis leidyi based on whole genome re-sequencing data. Initially, a total of 1,395 high quality SNPs were identified using stringent filtering criteria. From those, 192 assays were designed and validated, resulting in the final panel of 116 SNPs. Markers were diagnostic between the northern and southern M. leidyi lineages and highly polymorphic to distinguish populations. Despite using a reduced representation of the genome, our SNP panel yielded comparable results to using a whole genome re-sequencing approach (832,323 SNPs), recovering similar values of genetic differentiation between samples and detecting the same clustering groups when performing Structure analyses. The resource presented here provides a cost-effective, high throughput solution for population genetic studies, allowing to routinely genotype large number of individuals. Monitoring of genetic diversity and effective population size estimations in this highly invasive species will allow for the early detection of new introductions from distant source regions or hybridization events. Thereby, this SNP chip represents an important management tool in order to understand invasion dynamics and opens the door for implementing such methods for a wider range of non-indigenous invasive species.